E-COMMERCE RETAIL CUSTOMERS REPURCHASE FACTORS INFLUENCING IDENTIFICATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
With the fast-paced technological development era and the importance of using the Internet in our daily lives, e-commerce as shopping no longer seems new or unusual. Regardless of type or size, companies are using e-commerce advantage to compete in the market. Each of these companies needs a circle of independent and loyal customers. When the customer is satisfied, he gives positive feedback about the company and makes a repeat purchase. In this way, he attracts new customers to the company and provides an independent income for the company. Certain factors influence the customer's attitude and behavior. It is essential to determine what influences their customers' choices when competing to earn profit in the market; the customer must be satisfied in order for him to want to make a repurchase. Repurchases from customers indicate a loyalty to the company. Customer loyalty can be the result of a company consistently meeting and exceeding its customer expectations. Customer loyalty can have a significant impact on business growth. To assess and identify the factors influencing customer satisfaction, they are identified and offered a conceptual reflection of the current situation and offer a conceptual model of Identification Causes and Effects of Customer Satisfaction Framework (IceCSF) in e-commerce retail.